Examining Implementation of Tobacco Control Policy at the District Level: A Case Study Analysis from a High Burden State in India. (3rd January 2016) - Persai, Divya; Panda, Rajmohan; Gupta, Adyya
Abstract : Introduction. While extensive scientific evidence exists on the tobacco epidemic, a lack of understanding of both policies and their appropriate way of implementation continues to hinder effective tobacco control. This is especially so in the developing countries such as India. The present study aims to understand current implementation practices and the challenges faced in mainstreaming tobacco control policy and program. Methods. We chose a qualitative study design to conduct the case analysis. A total of 42 in-depth interviews were undertaken with seven district officials in six districts of Andhra Pradesh. A conceptual framework was developed by applying grounded theory for analysis. Analysis was undertaken using case analysis approach. Results and Discussion. Our study revealed that most program managers were unfamiliar with the comprehensive tobacco control policy. Respondents have an ambiguous opinion regarding integration of tobacco control program into existing health and development programs. Respondents perceive lack of resources, low prioritization of tobacco control, and lack of monitoring and evaluation of smoke-free laws as limiting factors affecting implementation of tobacco control policy. Conclusion. The findings of this study highlighted the need for a systematic, organized action plan for effective implementation of tobacco control policy and program.